Tracer Study Berbasis Website dengan menggunakan Metodologi Agile Framework Scrum - Fitriani, Leni; Setiawan, Ridwan; Anwar, Deviliana Nabila (Jurnal Algoritma, 2024)
In the current era of the industrial revolution, the need for human resources is increasingly stringent for skills that are in line with the latest technological developments. As an education provider, the Garut Institute of Technology strives to provide quality education to prepare alumni to be able to compete in the world of work. To get feedback from alumni, you need a way to get that information. Tracer study is an activity carried out by educational institutions to obtain information regarding the success of the educational process carried out by alumni. Apart from that, using the tracer study data can be used as evaluation material for educational institutions to improve learning and existing services. The Garut Institute of Technology, as a private university in Garut, which graduates hundreds of students each year, has carried out tracer study activities using the existing system. Based on the results of interviews conducted, there are system limitations in terms of monitoring in the form of the distribution of alumni who are already working and require a consultation feature which aims to be able to carry out online consultations regarding careers. The aim of this research is to build a web-based tracer study and build a tracer study system so that it can monitor alumni distribution and provide career-related consultations. This research uses the Agile methodology with the Scrum framework with the stages of requirements, product backlog, sprint planning, sprint, sprint review and sprint retrospective. By using system design modeling using Unified Modeling Language (UML). The results of this research are a system that can be used to determine the distribution of alumni and to provide feedback regarding the education received.